2021
DOI: 10.34287/mmt.2(49).2021.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the hemostasis system of cancer patients with thrombotic complications

Abstract: Surgical treatment of female genital cancer remains a rather difficult task in gynecological practice due to the possibility of thrombotic complications. It is important to study the features of hemostasis in such patients for the practical application of this knowledge. The aim of the study was to scientifically substantiate the features of hemostasis in patients with female genital cancer. Study materials: 103 patients with genital cancer who were treated. The purpose of the study. Coagulogram, colorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Recent studies have suggested that inflammation plays a key role in the initiation and progression of DVT, as well as in its association with cancer [ 12 , 13 ]. Inflammation can induce a hypercoagulable state by activating platelets, neutrophils, and endothelial cells and by modulating the expression and function of coagulation factors and inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that inflammation plays a key role in the initiation and progression of DVT, as well as in its association with cancer [ 12 , 13 ]. Inflammation can induce a hypercoagulable state by activating platelets, neutrophils, and endothelial cells and by modulating the expression and function of coagulation factors and inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation can induce a hypercoagulable state by activating platelets, neutrophils, and endothelial cells and by modulating the expression and function of coagulation factors and inhibitors. Therefore, inflammation-related biomarkers may be useful for predicting the risk of DVT in patients with cancer [ 12 ]. One such biomarker is the systemic immune-inflammation index (SII), which is calculated as the platelet count multiplied by neutrophil count divided by lymphocyte count [ 14 ].…”
Section: Introductionmentioning
confidence: 99%